Re-assessing Human Rights Issues in Palu Disaster Management - Tjitrawati, Aktieva Tri; Romadhona, Mochamad Kevin (Journal of Southeast Asian Human Rights, 2025)
In order to investigate the State's duty to provide fundamental rights in a State of exigency, this research aims to assess how the State implements human rights standards on disaster management and response in Indonesia. This study examines whether human rights standards have been included in Indonesian disaster management laws and regulations, as well as how these standards have been applied in the wake of the September 28, 2018, Palu tragedy. The inquiry was carried out through field research utilizing a standard questionnaire based on human rights implementation criteria, in compliance with The Core Humanitarian Standard on Quality and Accountability (CHS) 2014 standards. An FGD amongst stakeholders was held before the research to get more detailed and impartial information between the government and the disaster victims. Human rights standards are not being applied to disaster management in Palu, as evidenced by reports of victims being treated unfairly and inadequately supplied with necessities. According to the research's findings, there is a conflict between the State authority's propensity to apply positive-legalistic regulation of disaster management and the regulation's lax protection of human rights.